(untitled) (Research, Society and Development, 2021)
During COVID 19’s pandemic, cyber-attacks became constant. The aim of the study was to present the general law on data protection, information security and cyber-attacks during the COVID19 pandemic and to reflect the social impact of the measured attacks on society and organizations. In this qualitative review, the articles were selected from the Scielo and Google Scholar databases, and books were also selected for the development of the work. In view of the COVID-19 pandemic scenario, some attacks by hackers in Brazil were reported.